Time-Frequency Impact of Human Well-Being and Economic Growth on the Ecological Footprint: A Vietnamese Perspective - Ha Minh Hieu, (Asian Academy of Management Journal, 2023)
The nexus between natural resources and environmental degradation has significant implications. Nevertheless, this domain is insufficiently examined. This paper therefore a examines the time-frequency influence of economic growth, human development, and urbanisation on Vietnam’s ecological footprint (EF) using wavelet analysis. The findings showed that the intercorrelation between EF and related variables is statistically significant at low, medium, and high frequencies. More importantly, the elationships between these variables occur at a high frequency, which means that EF, economic growth (GDP), human development index (HDI), and urbanisation (UB) have different fluctuations in the long run. These outcomes are also confirmed by the wavelet-based Granger causality test at various time scales, which supports our relationship results